2021
DOI: 10.1002/ccr3.3721
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel implantable cardioverter‐defibrillator multisensor algorithm for heart failure monitoring in a COVID‐19 patient: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“… 18 Numerous individual case studies with HeartLogic capable devices and SARS‐CoV‐2 infections have also suggested that individual sensors may help identify patients who are COVID‐19 positive, even before patients themselves report symptoms. 19 , 20 , 21 , 22 The sensor changes reported in these individual cases are consistent with the quantitative trends that we report here, including increasing respiratory rate and impedance.…”
Section: Discussionsupporting
confidence: 89%
“… 18 Numerous individual case studies with HeartLogic capable devices and SARS‐CoV‐2 infections have also suggested that individual sensors may help identify patients who are COVID‐19 positive, even before patients themselves report symptoms. 19 , 20 , 21 , 22 The sensor changes reported in these individual cases are consistent with the quantitative trends that we report here, including increasing respiratory rate and impedance.…”
Section: Discussionsupporting
confidence: 89%
“…From our review of the literature, we found two case reports 8 , 9 and 2 case series 10 , 11 reporting the HL physiologic sensor changes, for a total of eight patients with SARS‐CoV‐2 infection. As represented in Table 1 , the patients were all infected by SARS‐CoV‐2 and even though only 3/8 patients had a more severe clinical manifestation with pneumonia, in 8/8 patients (100%) an increase in the ITI in association with an increase in the RR and a decrease in the activity level was present.…”
Section: Case Reportmentioning
confidence: 99%